Application of Risk Management and Patient Safety to Ensure Legal Protection for Patients and Health Personal Services in General Hospital of Abepura City of Jayapura - Hendrik William Rumbewas; Yovita Indrayati; Hadi Sulistyanto (SOEPRA, 2018)
The problem in this study is how to regulate and apply Risk Management and Patient Safety to ensure Legal Protection for Patient and Healthy Person at Abepura General Hospital, and what obstacles faced by Hospital in arranging and implementing Risk Management to ensure legal protection seen from involvement legal rules and technical aspects such as human resources, culture, politics, facilities and others. The purpose of the study is to obtain a description of the application, arrangement, and barriers pelksanaan Risk Management and Patient Safety to ensure the Legal Protection for Patients and Health Personnel at Abepura General Hospital, which is viewed from the side of involvement of the rule of law and the technical side such as human resources, culture, politics, facilities, and others.This research is an analytical, descriptive legal research, with the approach of Sociological Juridical, this research examines the problem of applying risk management and patient safety in giving legal protection to patient and health worker. To answer the problem, secondary date, primary date, and tertiary date are needed. Secondary date in the form of primary date collected through field study and secondary date collected by library study So the results of the study obtained on setting the hospital's internal rules in the form of hospital by low and operational standards used in hospitals has not functioned as a legal tool used to minimize the risk if there is a problem in RSUD Abepura, because the device rules still need penyempunaan material with takes a long time and adjusted to the ability and state of the hospital. Thus the form of risk must always be guarded by active regulatory oversight in providing periodic evaluations and monitoring. Implementation of risk management has not become a legal tool in use in supporting the Abepura Regional General Hospital service and has not become a key regulation in ensuring patient safety. Therefore, the local regulations are the basis of the guidelines in performing services to ensure patient safety and protect patients and health workers. So it has not yet illustrated the relationship between the implementation of risk management and patient safety due to the level of compliance with existing regulations and resulted in the form of misunderstanding between the patient, the patient's family, and the health worker. Obstacles to the implementation of risk management regarding the Normative side of the hospital has not understood the contents of regulations and policies on Patient Safety and not by the policy for patient safety cases in the hospital. From the technical side includes the function of coordination of service duties associated with several factors such as supporting facilities such as skilled health officers who supported facilities in the form of complementary facilities such as buildings and medical equipment which also become an obstacle in improving the quality of services in tunjang also with allocation funds that are not in accordance with the needs of the hospital, so that the escort to risk has not yet disputed the dispute between the patient and the health worker.